ANALISIS KEARIFAN LOKAL TERHADAP PEMBANGUNAN EKONOMI HIJAU DI KABUPATEN PASURUAN - Jati Batoro, Bambang Sutikno (Program Studi Ekonomi Syariah Universitas Yudharta Pasuruan, 2017)
Local culture or local wisdom is the values or behavior of local people living in interacting with the environment in which they live wisely. The purpose of this study is to analyze the relationship between local wisdom on green economy development in Pasuruan Regency. Research population is dairy farmer in Pasuruan Regency. The sample of this research dairy farmers in three districts in Pasuruan. Sampling using stratification random sampling with sample number 80 dairy farmer. Data analysis technique used is multiple linear regression analysis by doing t test. The results showed that local wisdom has a significant effect of 3,485 to green economic development in Pasuruan Regency.